Cost-eﬀective and high-impact sustainable vegetable farming utilizing low tunnel technology: a review - Krishna, Hare; Singh, S.K.; Sharma, Swati; Gowda, Manjunatha T.; Kumar, Rajeev; Panwar, Shreya; Pal, Govind; Bahadur, Anant; Tiwari, Shubham K.; Srivastava, Kuldeep; Karuppaiah, V.; Singh, A.K.; et al. (Current Horticulture, 2025)
The practice of low tunnel vegetable cultivation has emerged as a promising solution to address market ﬂuctuations and enhance farmers’ income by enabling oﬀ-season vegetable production. This method involves the use of miniature structures that mimic greenhouse conditions, providing protection and creating a favorable microclimate for vegetable crops. Low tunnels are constructed using locally available materials such as bamboo, wood, or metal bars covered with thin plastic sheets or nylon screens. These structures help conserve warmth, stimulate germination, and protect plants from adverse weather conditions, ultimately improving crop quality and yield. Plastic low tunnel technology, in particular, has proven to be a cost-eﬀective method for cultivating various vegetable crops, including cucurbits, melons, and cole crops, in winter season. By advancing the cropping season by 30-60 days and facilitating early market entry of the produce, low tunnels oﬀer signiﬁcant advantages to farmers, enabling them to capitalize on oﬀ-season demand and command higher prices for their produce. Additionally, low tunnel cultivation minimizes pest incidences and reduces pesticide consumption, making it an environmentally sustainable option for vegetable production. Studies have demonstrated the versatility of low tunnel construction techniques and materials, with various covering materials and support structures tailored to speciﬁc crop requirements and environmental conditions. The economic viability of low tunnel vegetable cultivation is further supported by high net returns and favorable beneﬁt: cost ratios recorded in comparative evaluations. Overall, low tunnel vegetable cultivation represents a promising technology for enhancing agricultural productivity, optimizing resource utilization, and improving farmer livelihoods, particularly in regions with extreme temperature regimes and ﬂuctuating market conditions.